1994
DOI: 10.1111/j.1399-6576.1994.tb03951.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and prolonged effects of pre– versus postoperative epidural analgesia with bupivacaine and morphine on pain at rest and during mobilisation after total knee arthroplasty

Abstract: Thirty-two patients scheduled for total knee arthroplasty were randomized to receive an identical epidural blockade initiated 30 min before surgical incision (N = 16), or at closure of the surgical wound (N = 16). Before induction of general anaesthesia the epidural catheter was tested with bupivacaine 7.5 mg.ml-1, 2 ml. General anaesthesia was induced with thiopentone, pancuronium or atracurium, and fentanyl 0.1-0.3 mg, and maintained with N2O/O2 and enflurane. The epidural regimen consisted of a bolus of 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…There were no significant differences in total analgesic consumption or pain scores by VAS and verbal scale during postoperative evaluation without evidences of preemptive effects. These same authors used a similar scheme of local anesthetics associated to opioids in patients submitted to total knee replacement and obtained the same results 65 . Katz et al 66 studied 30 patients submitted to thoracotomies with lumbar epidural fentanyl (4 µg.kg -1 ) before or after incision and observed a significant decrease in postoperative pain and drug consumption, thus evidencing preemptive analgesia.…”
Section: Epiduralsupporting
confidence: 58%
“…There were no significant differences in total analgesic consumption or pain scores by VAS and verbal scale during postoperative evaluation without evidences of preemptive effects. These same authors used a similar scheme of local anesthetics associated to opioids in patients submitted to total knee replacement and obtained the same results 65 . Katz et al 66 studied 30 patients submitted to thoracotomies with lumbar epidural fentanyl (4 µg.kg -1 ) before or after incision and observed a significant decrease in postoperative pain and drug consumption, thus evidencing preemptive analgesia.…”
Section: Epiduralsupporting
confidence: 58%
“…Gottschalk and Frank [9] found that intraoperative attenuation of noxious stimuli with epidural block reduced pain and wound hyperalgesia for three weeks after surgery in one patient. Flisberg et al [10] and Dahl et al [11] reported that epidural analgesia started in the postoperative period was as effective as epidural analgesia started preoperatively and continued into the postoperative period.…”
Section: Discussionmentioning
confidence: 98%
“…Clonidine [114] NS at rest or on movement compared with no clonidine Adrenaline [115] NS compared with no adrenaline Ropivacaine [30,92], bupivacaine [30,92] NS Timing of administration Oral and IV conventional NSAID [10] NS pre-+ postoperative vs postoperative administration Lumbar epidural bupivacaine plus opioid [116] NS pre-+ postoperative vs postoperative administration Lumbar epidural lidocaine plus ketamine plus morphine [111] Inconclusive results pre-vs post-incision Intra-articular bupivacaine [94] NS pre-vs postoperative techniques. The systemic analgesia trials compare active intervention groups of analgesics [paracetamol, conventional non-steroidal anti-inflammatory drugs (NSAID), COX-2-selective inhibitors, weak opioids, and strong opioids] with either a control or placebo group.…”
Section: Ns Components Of Spinal Solutionmentioning
confidence: 99%